Integrative medicine and the nutrition transition: What we learn from history and how it can be applied?. Issue 2 (August 2015) - Spedding, Simon; Best, Talitha
Abstract: History demonstrates how disease drives society to seek a remedy and industry refines this complementary medicine into a product. Researchers evaluate and modify the medicine before its acceptance by conventional medicine, often as a pharmaceutical. Whilst the accepted theory is that progress in conventional medicine is driven by medical research. Innovation in medicine is often driven by consumers and industry and acceptance by conventional medicine may incur substantial delays. This raises the question of whether a different construct is required recognising the value of integrating conventional medicines with traditional knowledge, and greater collaboration between the research, consumer, industry, and policy sectors. This paper describes new approaches to address the current health crisis of increasing rates of obesity and associated chronic disease, and explores the potential for health improvement through integration in medicine with collaborative partnerships between industry and research, acknowledging the pivotal position of consumers in setting the agenda for future research and the potential for policy makers to take action.